2022
DOI: 10.1161/circimaging.121.013200
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Left Ventricular Remodeling in Children With Valvar Aortic Stenosis Following Balloon Aortic Valvuloplasty

Abstract: Background: Aortic valve stenosis is the most common type of congenital left ventricular (LV) outflow tract obstruction. Balloon aortic valvuloplasty (BAV) has become the first-line treatment pathway in many centers. Our aim was to assess the trajectory of LV remodeling following BAV in children and its relationship to residual aortic stenosis (AS) and insufficiency (AI). Methods: Children <18 years of age who underwent BAV for isolated aortic stenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In a meta‐analysis by Hill et al, 16 survival, freedom from valve replacement, and freedom from reintervention at 10 years were 87%, 76%, and 46%, respectively, as compared with 89.9%, 85.9%, and 59.9% in our study. Also, the above‐mentioned study of Papneja et al 15 demonstrated a 10‐year reintervention‐free survival of 55%. Our survival analysis shows a significant difference between patients who required the BVPL in the neonatal period and those treated later.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a meta‐analysis by Hill et al, 16 survival, freedom from valve replacement, and freedom from reintervention at 10 years were 87%, 76%, and 46%, respectively, as compared with 89.9%, 85.9%, and 59.9% in our study. Also, the above‐mentioned study of Papneja et al 15 demonstrated a 10‐year reintervention‐free survival of 55%. Our survival analysis shows a significant difference between patients who required the BVPL in the neonatal period and those treated later.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study in neonates and children by Papneja et al 15 showed that well‐preserved LV function before the BVPL and a larger aortic valve annulus are associated with a lower risk of reintervention. The authors point out that this finding contrasts with previous studies, where a larger annulus was associated with a higher risk for developing aortic regurgitation, and speculate about the role of contemporary approach to use smaller balloons in children with larger annuli.…”
Section: Discussionmentioning
confidence: 99%